Inhibition of steel corrosion by calcium benzoate adsorption in nitrate solutions - Blustein, Guillermo (2005)
The inhibitive properties of calcium benzoate for steel corrosion were studied in sodium nitrate solutions at room temperature. Corrosion parameters of the steel/nitrate and steel/benzoate + nitrate interfaces were obtained from polarisation curves. Adsorption parameters of benzoate on steel in sodium nitrate solutions were determined through changes in the degree of surface coverage by the inhibitor, as a function of concentration, time and adsorption potential. The effect of chloride on the corrosion inhibition of benzoate was analysed exposing the metal in different chloride solution concentrations.